2021 Roadmap: electrocatalysts for green catalytic processes. (6th April 2021) - Liu, Jiandong; Ma, Jianmin; Zhang, Zhicheng; Qin, Yuchen; Wang, Yan-Jie; Wang, Yao; Tan, Rou; Duan, Xiaochuan; Tian, Tong Zhen; Zhang, Cai Hong; Xie, Wen Wen; Li, Nian-Wu; et al.
Abstract: Serious challenges in energy and the environment require us to find solutions that use sustainable processes. There are many sustainable electrocatalytic processes that might provide the answers to the above-mentioned challenges, such as the oxygen reduction reaction (ORR), water splitting, the carbon dioxide reduction reaction (CO2 RR), and the nitrogen reduction reaction (NRR). These reactions can enhance the value added by producing hydrogen energy through water splitting or convert useless CO2 and N2 into fuels and NH3 . These electrocatalytic reactions can be driven by high-performance catalysts. Therefore, the exploration of novel electrocatalysts is one of the important electrocatalytic fields. In this paper, we aim to systematically discuss a variety of electrocatalysts used for sustainable processes and to give further insights into their status and associated challenges. We invited many famous research groups to write this roadmap with topics including platinum (Pt) and its alloys for ORR, oxides for ORR, chalcogenides for ORR, carbon-based hollow electrocatalysts for ORR, carbides for ORR, atomically dispersed Fe–N–C catalysts for ORR, metal-free catalysts for ORR, single-atom catalysts (SACs) for ORR, metal boride (MB) electrocatalysts for water splitting, transitional metal carbides (TMCs) for water splitting, transition metal (TM) phosphides for water splitting, oxides for water splitting, sulfides for water splitting, layered double hydroxides for water splitting, carbon-based electrocatalysts for water splitting, Ru-based electrocatalysts for water splitting, metal oxides for CO2 RR, metal sulfides for CO2 RR, metals for CO2 RR, carbon for CO2 RR, SACs for CO2 RR, heterogeneous molecular catalysts for CO2 RR, oxides for NRR, chalcogenides for NRR, C3 N4 for NRR, SACs for NRR, etc. Their contributions enabled us to compile this 2020 roadmap on electrocatalysts for green catalytic processes and provide some suggestions for future researchers.